Wirtualna rzeczywistość jako narzędzie wspomagające zrozumienie świata osób ze spektrum autyzmu - Laska-Leśniewicz, Anna; Zwoliński, Grzegorz; Kamińska, Dorota (Życie z niepełnosprawnością w świecie VUCA, 2022)
Over the past few years, the rapid development of virtual reality (VR) has made the technology available to the common user. VR is used extensively in the entertainment industry, training tasks, medicine, tourism, architecture, art and many other fields. It also plays an increasingly important role in education and growing awareness and sensitivity of real social phenomena. The created VR application addresses the difficulties faced by people suffering from autism spectrum. Autism, a disorder that is diagnosed more and more frequently and, according to European data, occurs in 1% of the population (with a male to female ratio between 3: 1 and 4: 1) (Lai 2014; Loomes 2017). It is characterized by difficulties in social interactions, verbal and nonverbal communication, repetitive and stereotypical behaviours. Autism spectrum disorder is often associated with withdrawal and avoidance of contact with the world and people. The COVID-19 pandemic and the isolation associated with it have created an even greater separation between people on the spectrum and their surroundings. This article presents the use of virtual reality, which allows ordinary people to see the world of autism spectrum, and thus to better understand this different perception of the environment and the problems encountered in daily functioning of people with autism spectrum disorder. The created VR application increases the level of empathy among users, which positively affects the elimination of exclusion in a world full of uncertainty and variability.